Improving nurse initiated X‐ray practice through action research. Issue 4 (12th October 2016) - Thompson, Nadine; Murphy, Margaret; Robinson, John; Buckley, Thomas
Abstract: Introduction: Due to increasing demands on hospital Emergency Departments (EDs), the role of registered nurses, with additional training, has been extended to include requesting X‐ray examinations. The aim of this study was to evaluate nurse practice guidelines for requesting X‐rays in the ED setting and to utilise inter‐professional learning and change management theory to promote practice improvements. Methods: Three hundred and one nurse initiated X‐ray (NIX) requests were randomly selected between January and March 2012, and reviewed for observance of local department guidelines and quality of clinical history. The results of this preliminary review were used to inform the investigating team in order to improve and support practice. A collaborative educational intervention utilising inter‐professional learning and change management theory was implemented with an aim of improving the clinical history provided in NIX requests and development of a new policy to support clinical practice. A second review was repeated from February to April 2014 to evaluate the success of the educational intervention. Results: Observance of NIX guidelines improved from pre‐intervention to post‐intervention (48% vs. 90%, P > 0.001). Quality of clinical history also significantly improved in all four essential variable criteria: (1) mechanism of injury; (2) injury location; (3) side of injury; and (4) clinical question. Conclusion: This study demonstrates that utilising inter‐professional learning and change management theory can contribute to significant improvements in and support clinical practice of NIX in the emergency setting. Abstract : The aim of this study was to evaluate nurse practice guidelines for requesting X‐rays in the Emergency Department setting and to utilise inter‐professional learning and change management theory to promote practice improvements. This study outlines the advantage of implementing a collaborative educational intervention approach utilising inter‐professional learning and change management theory to support clinical practice, develop the quality of clinical history provided in X‐ray requests and improve patient care delivery.